Blood utilisation in a developing society: what is the best index of efficiency?. Issue 6 (30th April 2018) - Charles, K. S.; De Freitas, L.; Ramoutar, R.; Goolam, R.; Juman, S.; Murray, D.; Jhingai, R.; Chantry, A.
SUMMARY: Objectives: To assess blood usage for elective surgery in a developing country as a first step towards developing a maximum surgical blood‐ordering schedule (MSBOS). Background: Cross‐match:transfusion (C/T) ratio, transfusion index ( T i ) and transfusion ratio ( T %) are standard indices of efficient blood usage for elective surgical procedures. The MSBOS assigns surgical procedures to Group and Cross Match (GXM) and Group and Save (G&S) categories. Non‐use probability (NUP) is the percentage of blood that is requested but not used. Trinidad and Tobago (TTO) has a transfusion service that predominantly uses family replacement (F/R) donors. Materials/Methods: C/T ratio, T i, T % and NUP were retrospectively calculated for 304 elective surgical procedures performed at a tertiary medical institution in TTO between 1st January and 15th May 2013. Results: For 17 types of surgical procedure, C/T ratio was <2·5 for 10, T % ≥ 30 for 10 and T i ≥ 0·5 for 12, suggesting efficiency, significant blood use and a requirement for GXM for most operations. However, the majority of these procedures qualify for G&S when performed under conditions that guarantee ready access to blood in an emergency. A substantial proportion of issued blood was returned unused to the blood bank, giving an NUP of 39·7%. Conclusion: NUP was the most sensitive measure of efficiency. C/T ratio, T % and T i must be interpreted in the context of the blood donation system. An internationally accepted value of NUP that equates to efficient blood use should be adopted.